Correction to: Culturable bacteria associated with Anopheles darlingi and their paratransgenesis potential (Malaria Journal, (2021), 20, 1, (40), 10.1186/s12936-020-03574-1) - Rocha, Elerson Matos; Marinotti, Osvaldo; Serrão, Deidre Machado; Correa, Laura Viana; de Melo Katak, Ricardo; de Oliveira, Juan Campos; Muniz, Veranilce Alves; de Oliveira, Marta Rodrigues; do Nascimento Neto, Joaquim Ferreira; Pessoa, Marcos Cézar Fernandes; Roque, Rosemary Aparecida; da Mota, Adolfo Jose; et al. (Springer Nature, 2021)
Following publication of the original article [1], it came to the authors’ attention that the article had published with two author names misspelled: ‘Juan Campos de Oliveira’ had been written as ‘Campos-de-Oliveir Juan’, while ‘Joaquim Ferreira do Nascimento Neto’ had been written as ‘Joaquim Ferreira’. Please find the corrected names in the author list of this correction. The names have since been corrected in the published article.